The Oxford handbook of well-being and public policy - Adler, Matthew D.; Fleurbaey, Marc (New York, NY : Oxford University Press, 2016)
What are the methodologies that we should employ for designing and evaluating governmental policy, in light of the profound effects that policies have on the level and distribution of individuals' well-being? The Oxford Handbook of Well-Being and Public Policy is a comprehensive, interdisciplinary treatment of this question, drawing from welfare economics, moral philosophy, and psychology. It covers policy-assessment methodologies, both established and emerging, and reviews philosophical conceptions of well-being, and the literature on "subjective well-being" in psychology and economics. Further chapters focus specifically on well-being measurement, and a variety of challenges for policy assessment.
Introduction / Matthew D. Adler, Marc Fleurbaey -- Cost-Benefit Analysis / Robin Boadway -- GDP / Paul Schreyer -- Inequality and poverty measures / Frank Cowell -- Social Welfare Functions / John Weymark -- Fair allocation / William Thomson -- Multidimensional Indicators of Inequality and Poverty / Satya Chakravarty, Maria Ana Lugo -- QALY-Based Cost-Effectiveness Analysis / Jose Maria Abellan, Carmen Herrero, Jose Luis Pinto -- Happiness-Based Policy Analysis / Paul Dolan, Daniel Fujiwara -- Preference-based views of well-being / Krister Bykvist -- Mental State Approaches to Well-Being / Daniel M. Haybron -- Objective goods / Thomas Hurka -- Subjective well-being in psychology / Richard Lucas -- Subjective well-being in economics / Carol Graham -- Equivalent income / Marc Fleurbaey -- Extended preferences / Matthew D. Adler -- SWB as a Measure of Individual Well-Being / Andrew Clark -- The Capability Approach and Well-Being Measurement for Public Policy / Sabina Alkire -- Multidimensional Poverty Indices / Jean-Yves Duclos, Luca Tiberti -- Measuring Poverty / Thomas Pogge, Scott Wisor -- Does fairness require a multidimensional approach? / Richard J. Arneson -- Does the Choice of Well-Being Measure Matter Empirically? / Koen Decanq, Dirk Neumann -- Social Evaluation under Risk and Uncertainty / Philippe Mongin, Marcus Pivato -- Individual Responsibility and Equality of Opportunity / Francisco H. G. Ferreira, Vito Peragine -- Welfare Comparisons with Heterogeneous Prices, Consumption, and Preferences / Prasada Rao -- Welfare and the Household / Pierre-Andre Chiappori -- Preference Inconsistency / Eldar Shafir -- Lifetime Well-Being / Gregory Ponthiere -- The Well-Being of Future Generations / John Broome.
Includes bibliographical references and indexes.
Specialized.
Description based on online resource; title from home page (viewed on October 31, 2016).
Keywords: Well-being.; Quality of life -- Evaluation; Public welfare; Welfare economics; Social indicators; Economic indicators; Social policy; Economic policy